ANALISIS YURIDIS PENEGAKAN HUKUM TERHADAP PELANGGARAN HAM OLEH KELOMPOK KRIMINAL BERSENJATA (KKB) BERDASARKAN PERSPEKTIF HUKUM INDONESIA - Gultom, Yemima; Andika Surya Lebang (LPPM Universitas Putera Batam, 2024)
The responsibility of the Indonesian state in protecting the rights of victims of Human Rights Violations committed by Armed Criminal Groups (ACGs) involves various legal, judicial and rehabilitative efforts. Despite concerted action, challenges remain, including limited access to conflict areas, security concerns for investigators and victims, and complicated legal complexities. Improving inter-agency coordination, investing in increasing investigator capacity, and strengthening protection systems are critical to strengthening Indonesia's response to protecting victims of human rights violations. Prioritizing justice, rehabilitation and prevention is the basis for upholding victims' rights while facing complex challenges amidst the dynamics of conflict and security problems.